2002
DOI: 10.1002/jat.834
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water extracts from the surface of two Yew (Taxus) species on mites (Tetranychus urticae)

Abstract: Taxus cuspidata and Taxus media var. Hicksii contain paclitaxel, among other taxoids, on the surface of the needles. These compounds were removed by 5-s dipping of the needles in water just below its boiling point at 96 degrees C and at 60 degrees C and 40 degrees C. Taxus cuspidata contained a fourfold higher concentration of paclitaxel than Taxus media var. Hicksii. The extract with the higher concentration of paclitaxel was more harmful to the mites Tetranychus urticae Koch, increasing their mortality 150%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The parameters showed a similarity to those obtained for T. urticae developing on leaves treated with yew extract (Furmanowa et al ., 2001(Furmanowa et al ., , 2002. Mites treated with extracts either from yew needles or PAs showed a high mortality of juveniles, a decrease in female fecundity and a shortened longevity.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The parameters showed a similarity to those obtained for T. urticae developing on leaves treated with yew extract (Furmanowa et al ., 2001(Furmanowa et al ., , 2002. Mites treated with extracts either from yew needles or PAs showed a high mortality of juveniles, a decrease in female fecundity and a shortened longevity.…”
Section: Resultsmentioning
confidence: 97%
“…These authors demonstrated strong inhibition of the feeding activity of mites (by 28-35%) after treatment with sage extracts. In our previous study (Furmanowa et al ., 2001(Furmanowa et al ., , 2002 we found that Taxus needle extracts adversely affected most biological parameters responsible for mite population increase. They prolonged the duration of development, the mortality of developmental stages was increased and the fecundity of females was reduced by 60-70%.…”
Section: Introductionmentioning
confidence: 97%
“…[31,32]. It was determined that the extracts of yew showed a high mortality, decrease in female fecundity and shortened longevity [33,34]. Shi et al [35] revealed that the extract of Bassia scoparia (L.) A. J. Scott.…”
Section: Effect On Egg-laying Capacitymentioning
confidence: 99%
“…Although, extraction with water is the most effective for bulk application of plant extracts, one limitation is the level of stability of secondary compounds in the plant extracts. Furmanowa et al (2002) found that aqueous extracts of Taxus cuspidata Siebold & Zucc. stems and leaves have strong antifeedant activity against mites, but hot water extraction of this plant lowered the reproductive rate of T. urticae from 70.24 in the control to 6.70%.…”
Section: Discussionmentioning
confidence: 99%